2021
DOI: 10.1111/adb.13031
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression alteration identifies a novel circulating biomarker in serum exosomal for detection of alcohol dependence

Abstract: Alcohol dependence (AD) is one of the most common and detrimental neuropsychological disorders. Recently, more and more studies have focused on circular RNA as markers for central nervous system (CNS) diseases. The present study was conducted to evaluate the circular RNA expression alteration in serum exosomal and to identify a novel circulating biomarker for the detection of AD. We first isolated exosomes from serum and then investigated the circRNA expression alterations by high throughput whole transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…EVs have been acknowledged as participants in almost all physiological and pathological processes (35,36). The biological properties and functions of exosomes make them become potential biomarkers (37)(38)(39). Meanwhile, in terms of capturing biological information of the donor cells, exosomes are more specific and accessible compared to conventional biomarkers (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…EVs have been acknowledged as participants in almost all physiological and pathological processes (35,36). The biological properties and functions of exosomes make them become potential biomarkers (37)(38)(39). Meanwhile, in terms of capturing biological information of the donor cells, exosomes are more specific and accessible compared to conventional biomarkers (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…29,37 Circular RNAs are spliced endogenous RNAs that can potentially be used as diagnostic and prognostic biomarkers for disease. [38][39][40] Nevertheless, there were only a few studies have reported the diagnostic value of circRNAs in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome studies in the alcohol research field have revealed that alcohol use affects the expression patterns of hundreds of mRNAs and ncRNAs in the brain tissue of humans and animal models, e.g., see reviews and primary research articles (Contet, 2012;Nunez and Mayfield, 2012;Mayfield, 2017;Warden and Mayfield, 2017;Ferguson et al, 2019;Brenner et al, 2020;Drake et al, 2020). In addition to brain tissue, some studies have explored alcohol's effects in peripheral tissues including blood and saliva (Beech et al, 2012(Beech et al, , 2014Hicks et al, 2012;Kupfer et al, 2013;McClintick et al, 2014McClintick et al, , 2019Ignacio et al, 2015;Barr et al, 2016;Sureshchandra et al, 2016Sureshchandra et al, , 201910.3389/fnmol.2022.1032362 Ten Berg et al, 2018;Rosato et al, 2019;Lewis et al, 2021;Liu et al, 2021;Mead et al, 2021;Ferguson et al, 2022;Gong et al, 2022). These studies will be detailed in the following sections.…”
Section: Transcriptome Backgroundmentioning
confidence: 99%
“…Increasing evidence suggests that non-coding RNAs (ncRNAs) play a role in psychiatric disorders including AUD (Mayfield, 2017). The effects of alcohol on ncRNAs have been explored in both brain (Bohnsack et al, 2019;Drake et al, 2020) and peripheral tissues (Ignacio et al, 2015;Momen-Heravi et al, 2015;Barr et al, 2016;Sureshchandra et al, 2016Sureshchandra et al, , 2019Ten Berg et al, 2018;Rosato et al, 2019;Liu et al, 2021;Mead et al, 2021;Gong et al, 2022;Lewis et al, 2022). The studies identified in the literature search analyzed two types of ncRNAs in peripheral tissues: microRNAs and circRNAs.…”
Section: Non-coding Rnasmentioning
confidence: 99%